Colorimetric and fluorometric probes for the optical detection of environmental Hg(ii) and As(iii) ions. Issue 1 (9th December 2020) - Samanta, Tapendu; Shunmugam, Raja
Abstract : Human exposure to Hg(ii ) and As(iii ) can lead to several physiological problems such as liver damage, kidney damage, lung cancer, skin cancer, motion disorder, brain damage, etc . As a result monitor and identify of these elements are very much necessary. Abstract : Human exposure to Hg(ii ) and As(iii ) can lead to several physiological problems such as liver damage, kidney damage, lung cancer, skin cancer, motion disorder, brain damage, etc. To monitor and identify these harmful ions, throughout the years enormous effort has been put into the development of sensors. In this review, colorimetric and fluorometric chemical compounds (sensors) for Hg(ii ) (since 2015) and As(iii ) detection are described and discussed in detail. For Hg(ii ), sensors are divided on the basis of the compound's nature, such as heteroatom-based ligand-containing small molecules, rhodamine-based small molecules, reaction-based small molecules, and polymers. On the other hand, most As(iii ) ion sensors are based on H-bonding interactions.